The european clothing industry : meeting the competitive challenge - Taplin, Ian M.; Winterton, Jonathan, 1951- (Journal of Fashion Marketing and Management., 2004)
To provide an opinion as to the demise or metamorphosis of the UK clothing industry within the wider European context. Recently conducted research, along with a range of pertinent published (1978-2004) statistical data are used to inform the authors' viewpoint on the development of the UK clothing industry. The statistical evidence describing the change in import penetration, employment levels and the impact of the national minimum wage support the view that a new typology of the clothing industry is emerging from the ashes of a rapidly declined manufacturing base. Some of the detail of garmen.